Possibilities and restrictions of the implementation of mediation in domestic violence cases - Despotović-Stanarević Vera; Džamonja-Ignjatović Tamara (Temida)
This paper presents a model of the implementation of mediation in cases where a power disbalance between partners exists. The model includes relevant theoretical concepts which are important for understanding of violence phenomenon in the family, and the contemporary approaches to the work on balancing unequal power in relationships. In creating the model of family mediation in cases including violence, some basic concepts of mediation procedures are modified or adjusted (neutrality, confidentiality), as well as the concept of circular causality and complementary relationships from a systemic perspective. Implementation of interdisciplinary approach is proposed for efficient work on balancing the power in relations and using various working domains. The confession of violent behavior and the acceptance of personal responsibility by the offender, and the readiness of both sides to take part in restoration of a relationship are basic principles of restorative justice that is fundamental for victim- offender mediation. Therefore, those conditions are also necessary for a family mediation in cases including elements of violence, if the security for the victim is provided and guaranteed.